Pengaruh Komunikasi Efektif terhadap Loyalitas Guru di Sekolah Menengah Kejuruan Negeri Pertanian Terpadu Provinsi Riau - Siti Thohiroh; Syafaruddin Syafaruddin (Fakultas Tarbiyah dan Keguruan, 2020)
This research aimed at knowing the level of effective communication, teacher loyalty, and the influence of effective communication toward teacher loyalty at State Agriculture Integrated Vocational High School Riau Province. The data that were collected by questioner to 75 persons of samples were analyzed by using simple linear regression analysis technique, it was done by using SPSS 21.0 for Windows application program. Based on the analysis, it could be known that the correlation score (rxy) was 0.607 and Fhit (Fchange) was 42.489 with the significant level (p-value) 0.000 that was lower than 0.05. It was compared to rtable 0.227 at 5% significant level (n=75), so Ha was accepted and H0 was rejected. It showed that effective communication variable (X) influenced teacher loyalty variable (Y) significantly. The coefficient of determination (R square) based on the regression test result was 0.368, and it meant that 36.8% of teacher loyalty variable could be influenced by effective communication variable, and the rest 63.2% was influenced by other variables such as: compensation, working satisfaction, working participation, the health implementation, motivation, and others. Therefore, it could be stated that increasing teacher loyalty at State Agriculture Integrated Vocational High School Riau Province could be done by increasing the level of effective communication at the school.